Effect of hydrocolloids blends on frozen dessert "popsicles" made with whey concentrated. (January 2017) - Gajo, Adriano Alvarenga; de Resende, Jaime Vilela; Costa, Fabiano Freire; Pereira, Cristina Guimarães; de Lima, Renato Ribeiro; Antonialli, Fabio; de Abreu, Luiz Ronaldo
Abstract: The present study aim to investigate the physical and sensorial parameters of frozen dessert made with concentrated whey obtained through a nanofiltration process in total replacement of water and an ideal combination of hydrocolloids. The hydrocolloid mixtures were: T1 (guar/xanthan); T2 (guar/carrageenan); T3 (carrageenan/xanthan) and T4 (without hydrocolloids). Were evaluated the rheological behavior of the mixture, melting behavior, sensorial analysis, the initial freezing temperature, texture, and chemical composition of the concentrated whey. It was observed that different combinations of hydrocolloids influenced the viscosity of the mixture. On the melting behavior, the presence of hydrocolloids influences this parameter positively delaying the melting initial time of the frozen dessert. T1 and T4 resulted in the highest and lowest values of firmness respectively. The results of the sensory analysis showed that T1 and T2 were those that had the highest scores on the parameters of taste, texture, softness, appearance, purchase intention and overall impression. The correlation between sensory and instrumental data was proved using a multiple factor analysis. It was concluded that the combinations of guar and xanthan hydrocolloids are technologically the most appropriate on the application for formulations of frozen dessert made with concentrated whey considering the quality and acceptance standards. Highlights: Instrumental and sensory data were evaluated for popsicles made with concentrated whey. Different combinations of hydrocolloids influenced the viscosity of the mixture. Hydrocolloids delayed the melting initial time of the frozen dessert. Sensory descriptors were affected by added hydrocolloids. PCA showed correlation between sensory and instrumental variables.